Investigation of the Hierarchical Relationships between Challenges Faced by Pharmaceutical Industry, e-pharmacy and While Using Artificial Intelligence in Indian Pharmacy - Lakshay Aggarwal; Remica Aggarwal (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
While pharmacists are directly involved in patient care and work with existing drugs, pharmaceutical scientists create new drugs, therapies, and approaches to maximize benefits and established therapies. e-Pharmacy or online selling of medicines, helps patients and consumers get their medicines delivered to their doorsteps without having to leave their homes. Artificial intelligence [AI] and machine learning [ML] have revolutionized the industry and led to inventions, like virtual assistants, chat-bots, robotic treatment, and much more. The present research focuses on studying the various challenges faced by the pharmaceutical industry, e-pharmacy as well as the use of artificial intelligence in Pharmacy in India and further studying the hierarchical inter-relationships amongst them using VAXO technique based interaction and reachability matrices used in ISM-methodology.